Active commuting and obesity in mid-life: cross-sectional, observational evidence from UK Biobank. Issue 5 (May 2016) - Flint, Ellen; Cummins, Steven
Summary: Background: Physical inactivity is a leading cause of obesity and premature mortality. We aimed to examine the relation between active commuting and obesity in mid-life using objectively measured anthropometric data from UK Biobank. Methods: Cross-sectional, observational data from UK Biobank were used. These were collected from individuals aged 40-69 years who visited 22 assessment centres across the UK between 2006 and 2010. Self-reported commuting method was operationalised into seven categories, ordered to reflect typical levels of physical exertion. The outcomes assessed were BMI (based on objectively measured weight and height) and percentage body fat. Hypothesised confounders were income, area deprivation, urban or rural residence, education, alcohol intake, smoking, leisure physical activity, recreational walking, occupational physical activity, general health, and limiting illness or disability. We used sex-stratified multivariate linear-regression models. Findings: Final complete case sample sizes were 72 999 men and 83 667 women for the BMI outcome and 72 139 men and 82 788 women for the percentage body fat outcome. Active commuting was significantly and independently associated with reduced BMI and percentage body fat for both sexes, with a graded pattern apparent across the seven commuting categories. In fully adjusted models, compared with their car-only counterparts, mixed public and active transport commuters had significantly lower BMI (men: β coefficient −1·00 kg/m 2 [95% CI −1·14 to −0·87], p<0·0001; women: −0·67 kg/m 2 [–0·86 to −0·47], p<0·0001), as did cycling or cycling and walking commuters (men: −1·71 kg/m 2 [95% CI −1·86 to −1·56], p<0·0001; women: −1·65 kg/m 2 [–1·92 to −1·38], p<0·0001). Similarly, compared with car-only commuters, mixed public transport and active commuters had significantly lower percentage body fat (men: −1·32% [95% CI −1·53 to −1·12], p<0·0001; women: −1·10% [–1·40 to −0·81], p<0·0001), as did cycling or cycling and walking commuters (men: −2·75% [95% CI −3·03 to −2·48], p<0·0001; women: −3·26% [–3·80 to −2·71], p<0·0001). Interpretation: This study is the first to use UK Biobank data to address the topic of active commuting and obesity and shows robust, independent associations between active commuting and healthier bodyweight and composition. These findings support the case for interventions to promote active travel as a population-level policy response for prevention of obesity in mid-life. Funding: UK Medical Research Council.